(3eYQaI CQJaGY GdCTNGU GdbGFeI hCYeOI GdLHGd hCQJaGY GdZjhes - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3faQV Cf CH GQJaGY LHd ChTNU hfQjO Cf fYdeg afbje TNUkG Ydi hLg GdGQV eKd O g` s
(3BNQgG (B:s
(3hjbSe Ydi eG Hjf GdXdjf ef GdCabjf JMUd ebOGQ GdTNU GdeWdhH GQJaGYg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdg GdKGfjIs
(3HgG fXGe GdJYbjHIs
(3hHgG QSe gfOSis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B617 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs